2020
DOI: 10.3390/healthcare8030269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Functional Oral Intake Scale (FOIS) and the Self-Efficacy Scale among Cancer Patients: A Cross-Sectional Study

Abstract: A few studies have provided detailed reports suggesting that subjective swallowing disorders may be related to dysphagia. Therefore, we verified the relationship between oral health-related self-efficacy and dysphagia severity in cancer treatment using a cross-sectional study. Participants included patients undergoing treatment for cancer at Shimane University Hospital in Shimane, Japan, and those receiving outpatient treatment at the hospital’s Oral Care Center between August 2018 and April 2019. In all, 203 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This will strengthen the patient's confidence in rehabilitation, actively promote self-management of behavior for patients with dysphagia, so as to achieve the effect of preventing aspiration pneumonia and improving the patient's quality of life. Based on the Jonckheere-Terpstra test; SEAC and OSEC tend to increase along with the development of the FOIS category (Matsuda et al, 2020). In conclusion, self-efficacy plays an important role in dysphagia and can influence the severity of dysphagia of patients.…”
Section: Discussionmentioning
confidence: 83%
“…This will strengthen the patient's confidence in rehabilitation, actively promote self-management of behavior for patients with dysphagia, so as to achieve the effect of preventing aspiration pneumonia and improving the patient's quality of life. Based on the Jonckheere-Terpstra test; SEAC and OSEC tend to increase along with the development of the FOIS category (Matsuda et al, 2020). In conclusion, self-efficacy plays an important role in dysphagia and can influence the severity of dysphagia of patients.…”
Section: Discussionmentioning
confidence: 83%
“…Notably, it has previously been correlated with other patient-reported measures of swallowing and self-efficacy among head and neck cancer cohorts. 15,16 Our subgroup analysis found that while patients who underwent adjuvant therapy (adjRT/CRT) recovered to near-normal levels of oral intake (median FOIS = 6) within 1-year, they are more likely to have persistent dysphagia and be PEG tube dependent at 1 year after surgery rates compared with NAT patients (p < 0.04). In contrast, NAT patients rapidly achieve near-normal oral intake by their 3-month follow-up and maintain normal feeding after 1 year.…”
Section: Effects Of Adjuvant Radiotherapy On Swallowing Outcomes In T...mentioning
confidence: 86%
“…Treatment information included date of TORS surgery, neck dissection, dates of chemoradiotherapy, and length of percutaneous endoscopic gastronomy (PEG) and nasogastric (NG) tube placement. The Functional Oral Intake Scale (FOIS) is a validated measure of swallowing and nutritional status and was obtained at pre‐operative visit, first post‐operative visit, between end‐of‐treatment (EOT) and 1 year after surgery, and at most recent follow‐up visit 26–28 . FOIS was clinician‐assessed and defined on a scale of 1–7, with 1 representing no oral intake and 7 representing total oral intake with no restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…The Functional Oral Intake Scale (FOIS) is a validated measure of swallowing and nutritional status and was obtained at preoperative visit, first post-operative visit, between end-oftreatment (EOT) and 1 year after surgery, and at most recent follow-up visit. [26][27][28] FOIS was clinician-assessed and defined on a scale of 1-7, with 1 representing no oral intake and 7 representing total oral intake with no restrictions. When available, SLP evaluations were used to assess presence of swallowing impairment, signs of aspiration on a clinical swallowing trial, and if aspiration was confirmed using fiberoptic endoscopic evaluation of swallowing (FEES) or barium swallow study.…”
Section: Outcome Measuresmentioning
confidence: 99%